2015
DOI: 10.1111/jan.12655
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of climate and environmental issues: a qualitative study

Abstract: Aim. The aim of this study was to explore nurses' perceptions of climate and environmental issues and examine how nurses perceive their role in contributing to the process of sustainable development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 21 publications
8
74
1
1
Order By: Relevance
“…5) The level of priority assigned by healthcare staff to sustainable healthcare was suggestive that due to the emotional demands of the job, staff perceived that they had little emotional resilience left for environmental issues (Dunphy, 2013). 6) Individual and social barriers were associated with an externalisation of blame, with lack of leadership, inaction of others and selfexoneration all cited as reasons for a lack of engagement (Anåker, Nilsson, Holmner and Elf, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5) The level of priority assigned by healthcare staff to sustainable healthcare was suggestive that due to the emotional demands of the job, staff perceived that they had little emotional resilience left for environmental issues (Dunphy, 2013). 6) Individual and social barriers were associated with an externalisation of blame, with lack of leadership, inaction of others and selfexoneration all cited as reasons for a lack of engagement (Anåker, Nilsson, Holmner and Elf, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Consideration of global warming from a global perspective was not seen as important within care and emphasis was placed upon environmental issues within the ward and hospital (Anåker et al, 2015). Kirk (2002) describes this egocentric focus, suggesting that nursing models have focussed on the immediate environment neglecting global thinking.…”
Section: Endemic Blindness To 'Global' Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Engaging nursing professionals is particularly crucial, as they have wide opportunities to minimize unnecessary consumption, and physicians, who can avoid unnecessary treatment days. Recent studies have reported that nurses saw pro-environmental behavior as secondary to other job requirements [12,15] and even the term health care professionals' environmental numbness has been used. [10] This has been explained with medical procession, along with which health care professionals have increasingly concentrated on patients' immediate needs rather than preventative scope including protection of environmental health.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
“…[2,9,14] Indeed, environmental responsibility refers to people's behavior, [3,4] but it also includes the actions taken by organizations to protect the world around them. [4,[15][16][17] Environmental responsibility is also an important part of occupational wellbeing, as chemical control protects workers' health. [11,18,19] Health care has been identified as a "highhazard" work sector because of the pharmaceuticals involved, such as anticancer drugs, sterilizing substances, and other substances used in various forms by its employees.…”
Section: Introductionmentioning
confidence: 99%